PENGARUH KUALITAS PELAYANAN PASTI PASS DI SPBU 44.522.20 BANGSRI KABUPATEN BREBES (CV. BERKAH) TERHADAP KEPUASAN PELANGGAN - Sri Ratih Handayani (Jurnal Strategik, 2017)
This study entitled The Effect of Service Quality PASTI PASS at Bangsri 44,522.20 Gas Station in Brebes Regency (Blessing CV) Against Customer Satisfaction. The objectives to be achieved in this study are: 1. To find out whether PASTI PASS service quality has a significant effect on customer satisfaction at SPB 44,522.20 Bangsri Brebes Regency. 2. To find out how much influence PASTI PASS service quality has on customer satisfaction at SPB 44,522.20 Bangsri Brebes Regency. The research method used is a case study at the 44,522.20 Bangsri gas station in Brebes Regency, while the data collection method used is survey, interview, library research questionnaire. In testing the hypothesis used a simple regression coefficient analysis tool with t and F. From the analysis results can be concluded: 1. There is a significant influence between PASTI PASS service quality on customer satisfaction. Based on F test statistical analysis by using a confidence level of 95% (α = 0.05) and degree of freedom (df) = (k - 1) and (n - k - 1) obtained by Ftable of 2.71 the results of calculations performed produce Fcount 954,093. Because Fcount is greater than Ftable, the hypothesis Ho is rejected, and the t test. By using a confidence level of 95% (α = 0.05) and the degree of freedom (df) = K and (n - k - 1) obtained t table of 1.6609. From the calculation performed, the value of the service tcount is 30,888, because the tcount is greater than t table (30,88> 1,6609), then the service variable (X) has a significant effect on customer satisfaction. 2. From the results of simple linear regression calculation, Y = 1.012 + 0.982 X means that the value of customer satisfaction will be positive at 1.012 if the service variable (X) is constant. This means that customers still have satisfaction to make purchases without any changes in service quality variables, and if the service variable (X) increases by one unit, it will increase customer satisfaction (Y) by 0.982 units. Keywords: service quality, customer satisfaction